Vacancy‐Enabled O3 Phase Stabilization for Manganese‐Rich Layered Sodium Cathodes. Issue 15 (1st March 2021) - Xiao, Biwei; Wang, Yichao; Tan, Sha; Song, Miao; Li, Xiang; Zhang, Yuxin; Lin, Feng; Han, Kee Sung; Omenya, Fredrick; Amine, Khalil; Yang, Xiao‐Qing; Reed, David; et al.
Abstract: Manganese‐rich layered oxide materials hold great potential as low‐cost and high‐capacity cathodes for Na‐ion batteries. However, they usually form a P2 phase and suffer from fast capacity fade. In this work, an O3 phase sodium cathode has been developed out of a Li and Mn‐rich layered material by leveraging the creation of transition metal (TM) and oxygen vacancies and the electrochemical exchange of Na and Li. The Mn‐rich layered cathode material remains primarily O3 phase during sodiation/desodiation and can have a full sodiation capacity of ca. 220 mAh g −1 . It delivers ca. 160 mAh g −1 specific capacity between 2–3.8 V with >86 % retention over 250 cycles. The TM and oxygen vacancies pre‐formed in the sodiated material enables a reversible migration of TMs from the TM layer to the tetrahedral sites in the Na layer upon de‐sodiation and sodiation. The migration creates metastable states, leading to increased kinetic barrier that prohibits a complete O3‐P3 phase transition. Abstract : O3 to P3 phase transition in layered sodium cathode materials induces large volume change and is detrimental to the performance. This work shows that the creation of transition metal and oxygen vacancies in the layered material can trigger multiple metastable intermediate phases, which substantially prohibits the O3 to P3 phase transition and enables high‐performance Na and Mn‐rich layered materials.